Triassic alkaline basalts of the Ischigualasto-Villa Union Basin, La Rioja and San Juan provinces. - Page, S. (1997)
The Ischigualasto-Villa Union basin developed as a consequence of processes taking place at the transition between Sierras Pampeanas and Precordillera, together with the Gondwana extension and ultimate break-up since the Upper Palaeozoic-Triassic (Lower Jurassic ?). In the Ischigualasto region the basin is characterized by accumulations of continental sediments and contemporaneous mafic magmatic rocks. This paper presents data on the basalts and trachytes, which are alkaline rocks of the basalt-trachybasalt-trachyte series. Petrology indicates high pressure and temperature involving the fractionation of olivine, magnetite (Ti-magnetite), ilmenite, cpx, Ca feldspar and apatite. Flows were extruded through fracture-related vents and/or monogenetic volcanoes constructed of piles of thick and viscous lavas. These rocks seem to correspond and are interpreted as being the product of fast magmatic ascent and subsequent intrusion or flow. Temporary storage in smaller chambers at intermediate depth could have been the mechanism for the differentiation process.